COMPUTATIONAL DRUG DISCOVERY OF POTENT ANTIMALARIAL XANTHONES: A SYSTEMATIC REVIEW AND ADMET-GUIDED IDENTIFICATION OF A LEAD CANDIDATE - Joanne Theophilia Winata; Komang Dian Aditya Putra; Yosi Bayu Murti; Akhmad Kharis Nugroho (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2025)
Background: Artemisinin resistance mediated by Kelch13 mutations threatens malaria elimination efforts. Xanthones from Garcinia mangostana present a promising alternative scaffold for antimalarial drug development. Objective: This study systematically identified potent xanthones reported in the literature and evaluated their pharmacological potential using computational methods. Methods: A comprehensive systematic review was conducted across PubMed, Scopus, and Wiley Online Library (through September 2025) following PRISMA 2020 guidelines, searching for